PSX-6 Effect of dietary microalgae and fish oil on the nursery pig acute-phase response. (7th December 2018) - Lee, A; You, L; Li, Z; Oh, S; Alcorn, M; Zhu, J; Fisher-Heffernan, R; Regnault, T; Huber, L; Karrow, N
Abstract: Piglet performance can be adversely affected by stress at weaning. Dietary supplementation with omega-3 polyunsaturated fatty acids (n-3 PUFA) reduces inflammatory stress, and may promote piglet health and growth. Fish oil (FO) is considered a major source of n-3 PUFA; however, microalgae (AL) may be a more sustainable alternative. The aim of this study was to assess the health benefits of supplementing nursery pigs with AL (All-G-Rich, Aurantiochytrium limacinum biomass containing 70% crude fat and 17% DHA) or FO. Seventy-two cross-bred piglets were placed on a low-quality protein diet supplemented with either 1.25% FO or 3.12% AL (equal in n-3 PUFA), or 5% corn oil as a control (CON) for three weeks (feeding phases 1 and 2), followed by a common diet for three weeks (feeding phase 3). At the end of phase 2 feeding, 8 pigs per treatment underwent an i.m. LPS immune stress challenge, and the acute-phase response was assessed. Eight pigs per treatment were also vaccinated with two novel antigens throughout the feeding trial, and the antigen-specific acquired immune response was assessed. No significant differences in piglet average daily gain were observed, but the FO piglets had a decreased feed intake when placed on the common diet. While both AL and FO supplementation attenuated the LPS-induced fever response, only AL pigs had an attenuated cortisol response and exacerbated the pro-inflammatory cytokine responses (TNF-α, IL-1β, and IL-6); the IL-10 response in the AL treatment was also augmented compared to the FO treatment. Chromogranin A levels were also greater in AL pigs compared to FO and CON pigs at 15 min following LPS challenge. The acquired immune response was unaffected by the dietary treatments. Results suggest that AL or FO supplementation in nursery diets differentially modulated the acute-phase response, possibly due to differences in n-3 PUFA profile.